Leave or stay? A narrative inquiry of tensions in novice English teachers’ professional identity construction at China’s private universities - Xiangchen Zhang; Xiangchen Zhang (Frontiers in Psychology)
Novice English teachers at China’s private universities are easily confronted with tensions when they constructed the professional identity in the early career stage. Drawing on a theoretical framework of social identity theory, self-discrepancy theory and situated learning theory, this narrative inquiry study explored the causes, manifestations, and solutions to teachers’ professional identity tensions through in-depth interviews. Data were interpreted through metaphorical biographies and thematic analysis. Results show that tensions were caused by discrepancies among three self-concepts and conflicts between the English teacher identity and the private university teacher identity. In tensions, many aspects of participants’ professional identities were impaired and they unfulfilled the organizational identification. Participants reconciled three selves and adopted two approaches (assimilation and dissimilation) to navigate PI tensions. Policy makers are suggested to offer a well-established identity policy and sufficient research funding to facilitate the academic development of both private universities and teachers there. Private universities are suggested to provide diverse supports to teachers for their career development. Novice teachers could take the initiative of adapting to the culture and regulations of private universities and combine their research interest with the working context.